Automated storage and active cleaning for multi-material digital-light-processing printer. Issue 5 (10th June 2019) - Matte, Christopher-Denny; Pearson, Michael; Trottier-Cournoyer, Felix; Dafoe, Andrew; Kwok, Tsz Ho
Abstract : Purpose: The purpose of this paper is to introduce a novel technique for printing with multiple materials using the DLP method. Digital-light-processing (DLP) printing uses a digital projector to selectively cure a full layer of resin using a mask image. One of the challenges with DLP printing is the difficulty of incorporating multiple materials within the same part. As the part is cured within a liquid basin, resin switching introduces issues of cross-contamination and significantly increased print time. Design/methodology/approach: The material handling challenges are investigated and addressed by taking inspiration from automated storage and retrieval systems and using an active cleaning solution. The material tower is a compact design to facilitate the storage and retrieval of different materials during the printing process. A spray mechanism is used for actively cleaning excess resin from the part between material changes. Findings: Challenges encountered within the multi-material DLP technology are addressed and the experimental prototype validates the proposed solution. The system has a cleaning effectiveness of over 90 per cent in 15 s with the build area of 72 inches, in contrast to the previous work of 50 per cent cleaning effectiveness in 2 min with only 6 inches build area. The method can also hold more materials than the previous work. Originality/value: The techniques from automated storage and retrieval system is applied to develop a storage system so that the time complexity of swapping is reduced from linear to constant. The whole system is sustainable and scalable by using a spraying mechanism. The design of the printer is modular and highly customizable, and the material waste for build materials and cleaning solution is minimized.